2020
DOI: 10.3390/healthcare8020102
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Issues in Head and Neck Cancer Patients

Abstract: The purpose of this paper is to update the oncologist on the correct approach to the nutritional care of the head and neck cancer patient. Recent scientific contributions on this issue, with a special emphasis on international guidelines and randomised clinical trials (RCTs), are reviewed. The following points are noteworthy: 1. Despite the advances in early diagnosis and modern treatment of head and neck cancer, this tumour still ranks first regarding frequency and severity of weight loss, both at the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
3
1
1
Order By: Relevance
“…Patients with a higher OCC Factor 3 showed less treatment interval TBM loss, including the loss of both LBM and ASM, but they also showed more deaths within 2 years ( Table S2 and Figure 3 ). This observation is different from that of previous studies reporting that pretreatment or treatment interval muscle loss induced by cancer or chemotherapy is associated with poor treatment outcomes in patients with cancer [ 79 , 80 , 81 , 82 , 83 ]. The patients were older, received a greater daily calorie supply, underwent feeding tube treatment for a longer duration, and even failed to develop TFM loss during CCRT, as compared to patients with a low OCC Factor 3 ( Table S2 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with a higher OCC Factor 3 showed less treatment interval TBM loss, including the loss of both LBM and ASM, but they also showed more deaths within 2 years ( Table S2 and Figure 3 ). This observation is different from that of previous studies reporting that pretreatment or treatment interval muscle loss induced by cancer or chemotherapy is associated with poor treatment outcomes in patients with cancer [ 79 , 80 , 81 , 82 , 83 ]. The patients were older, received a greater daily calorie supply, underwent feeding tube treatment for a longer duration, and even failed to develop TFM loss during CCRT, as compared to patients with a low OCC Factor 3 ( Table S2 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In HNC patients, including NPC, inadequate dietary intake is associated with various symptoms, including dysphagia, odynophagia, and anorexia, which can lead to weight loss. During cancer therapy, such as chemotherapy, radiotherapy, or a combination of both, the development of mucositis, xerostomia, dysphagia, dysgeusia, and depression can lead to decreased dietary intake, weight loss, and 20% of patients withdraw from therapy 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it causes treatment breaks with a higher economic burden and decreased functional performances that cumulatively lead to decreased quality of life and higher mortality rates. Interestingly, overweight and obese people with higher BMIs are at the same risk of all of the mentioned complications [6,13,[25][26][27]. Hence, studies have shown that weight loss before treatment was one of the main independent survival predictors, while nutritional support before surgery can lead to significant beneficial changes in quality of life with fewer postoperative infectious complications [28,29].…”
Section: Introductionmentioning
confidence: 99%